Deposit insurance: Pricing and incentives - Eelis Hein (Bank of Finland, 1996)
This study analyzes the valuation and bank risk incentive effects of deposit insurance using an approach based on options theory. While the value of deposit insurance can obviously be set under existing regulatory measures such as capital adequacy and reserve requirements, the actual and expected behaviour of the regulator is shown to exert an effect on bank risk policy, and thus, on the stability of the banking sector.The following factors are identified as possible causes of increased preference for risk on the part of banks: · an expectation that in the event of insolvency the deposit insurance will cover claim holders not otherwise initially insured; · an expectation on the part of shareholders that they are not threatened with losing their position; and · underpricing of deposit insurance premium in relation to a bank's market-valued capital adequacy. These expectations increase preference for higher risk because they remove both the need for debt holders to require any risk premium for their investment and the threat that shareholders might lose their participation in the bank's future earnings.Thus, banks are not "penalized" for taking on risk.Instead, the costs of higher risk are borne by the deposit insurer, which in Finland's case, is ultimately the government and taxpayers.A related issue is that the efficiency of the bank inspection authority seems to affect the risk-taking behaviour of banks (i.e. if a bank believes that the bank inspection authority is incapable of determining its true financial condition and actual risk exposure, it has incentive to take a riskier position). Using bank stock prices, point estimates of the value of deposit insurance are calculated for listed Finnish banks between 1987-1993.The results indicate that the value of the insurance has varied among banks and over time.Generally, charged deposit premia have been underpriced in comparison to the risk position of the studied banks.Thus, one consequence of the shakeout in Finland's banking sector appears to be that a sizable wealth transfer from the government to bank shareholders has taken place.
URN:NBN:fi:bof-201408071680
Keywords: 330; Banking; Deposit Insurance; Risk Incentives; Option Pricing; Regulatory Behaviour